Association of DNA Repair XRCC1 Gene Polymorphism with Leukemia - Sana, Wasfa; Abid ur Rehman; Ahmed, Bisma; Sayeed, Md Abu; Farooq, Mashhood uz Zafar (Indus Journal of Bioscience Research, 2024)
A group of cancerous diseases of the blood and bone marrow known as leukemias are life-threatening. It is crucial to recognize the leukemic cells lineage when making a diagnosis of leukemia because treatment for the disease depends on whether the cells are myeloid or lymphoid. As per the Observation There is total 300 blood samples in which 150 were leukemic patients and 150 were healthy person. The genotype distribution frequencies of the XRCC1 gene’s SNP rs25487 results demonstrate a highly significant connection between heterozygous (GA) rs25487 of the XRCC1 gene and an increased risk of leukemia up to 2-folds (OR=2.52; 95% CI=1.51- 4.20; p=0.0004). The scenario is identical when it comes to homozygous mutant (AA), which also shown a highly significant connection with a reduced risk of leukemia and performs a protective role (OR=0.40; 95% CI=0.23-0.70; p=0.0014). The combined genotype model of mutant and hetero of rs25487 demonstrated a weakly non-significant correlation with leukemia (OR=1.14; 95% CI=0.72-1.82; p=0.5618). This study intended to look at the connection between leukemia risk regulation and XRCC1 polymorphisms, as well as the conceivable relationship between leukemia patients and the XRCC1 polymorphism (rs25487). It was determined that rs25487 was linked to a higher risk of leukemia in people